2016
DOI: 10.1111/1460-6984.12214
|View full text |Cite
|
Sign up to set email alerts
|

Influence of current input–output and age of first exposure on phonological acquisition in early bilingual Spanish–English‐speaking kindergarteners

Abstract: Current input-output appears to be a better predictor of phonological accuracy than age of first English exposure for early bilinguals, consistent with findings on the effect of language experience on performance in other language domains in bilingual children. Although greater current input-output in a language predicts higher accuracy in that language, this interacts with sound complexity. The results highlight the utility of the EML classification in assessing bilingual children's phonology. The relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 52 publications
(154 reference statements)
4
15
0
2
Order By: Relevance
“…On the other hand, the studies that found no link between maternal education and children's Spanish outcomes focused on Mexican-American participants (DeAnda et al, 2016;Friend et al, 2017) and on more heterogeneous samples A final important result of this study was that whereas English skills grew significantly over one year for children of more and less educated mothers, more limited growth was observed in Spanish; indeed, Spanish phonological and lexical measures remained quite unchanged between 3;6 and 4;6. This finding confirms the results of previous studies that document an accelerated growth in English after entering preschool but a deceleration in the development of Spanish among dual language learners growing up in the U.S. (Hoff, Quinn & Giguere, 2017;Hoff et al, 2018;Montanari et al, 2018;Montanari et al, 2019;Ruiz-Felter, Cooperson, Bedore, & Peña, 2016;Hammer, Lawrence & Miccio, 2008). Despite this uneven development, there was no significant interaction of child age and maternal education for either English or Spanish language measures, suggesting that age and maternal education effects were independent of each other.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the studies that found no link between maternal education and children's Spanish outcomes focused on Mexican-American participants (DeAnda et al, 2016;Friend et al, 2017) and on more heterogeneous samples A final important result of this study was that whereas English skills grew significantly over one year for children of more and less educated mothers, more limited growth was observed in Spanish; indeed, Spanish phonological and lexical measures remained quite unchanged between 3;6 and 4;6. This finding confirms the results of previous studies that document an accelerated growth in English after entering preschool but a deceleration in the development of Spanish among dual language learners growing up in the U.S. (Hoff, Quinn & Giguere, 2017;Hoff et al, 2018;Montanari et al, 2018;Montanari et al, 2019;Ruiz-Felter, Cooperson, Bedore, & Peña, 2016;Hammer, Lawrence & Miccio, 2008). Despite this uneven development, there was no significant interaction of child age and maternal education for either English or Spanish language measures, suggesting that age and maternal education effects were independent of each other.…”
Section: Discussionsupporting
confidence: 90%
“…However, over the course of one year, the participants made gains in proficiency in both languages, with growth in English being more evident than growth in Spanish. This finding confirms the results of previous studies that document an accelerated growth in English after entering preschool but a deceleration in the development of Spanish among dual language learners growing up in the US (Hoff et al, 2018;Ruiz-Felter et al, 2016;Scheffner-Hammer et al, 2008). Interestingly, the results showed no relation between most proficiency measures and language mixing patterns, with the exception of TNDW in English and language choice at age 3;6.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, the children produced more English unique words at age 4;5 (M = 109.00) than at age 3;6 (M = 68.32) (t(24) = -5.58, p < .001, d = 1) (large effect size). Overall, these results suggest that the children made gains in proficiency in both languages over the course of one year; however; growth was more evident in English than in Spanish, as found in other studies of young dual language learners growing up in the US (Hoff, Quinn, & Giguere, 2018;Ruiz-Felter, Cooperson, Bedore, & Peña, 2016;Scheffner-Hammer, Lawrence, & Miccio, 2008). Language mixing as related to age, language, and proficiency A series of 2 (language) by 2 (age) ANOVAs was used to evaluate main effects and language by age interaction effects on inter-sentential, intra-sentential, and total language mixing.…”
Section: Resultssupporting
confidence: 78%
“…Language input and language use have been empirically shown to affect bilingual children's oral language abilities; however, the effects of these variables on language outcomes seem to depend on how they are defined and estimated. For example, estimates of cumulative exposure, calculated by determining when the child was first exposed to a language, do not correlate as well with oral language or phonological skills as do estimates of concurrent daily language use and exposure (Bedore et al, 2012;Bohman, Bedore, Peña, Mendez-Perez, & Gillam, 2010;Cooperson, Bedore, & Peña, 2013;Gutierrez-Clellen & Kreiter, 2003;Ruiz-Felter, Cooperson, Bedore, & Peña, 2016). Cooperson et al (2013) found that percent of English input-output predicted 2.6% of the unique variance in English phonological accuracy, whereas age of first exposure was not significantly related.…”
Section: Language Input and Usagementioning
confidence: 99%